(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
This study critically analyzes Volodymyr Zelenskiy’s speech to the UK Parliament using Norman Fairclough’s 3D model of Critical Discourse Analysis (CDA). It examines how textual, discursive, and social practices are constructed to exercise power and shape perceptions during the Russia? Ukraine conflict. Using a qualitative approach, the findings reveal that Zelenskiy’s strategic use of language significantly influenced audience sentiment, positioning Ukraine as a victim of aggression and Russia as the aggressor. The study highlights the potent role of language in constructing political reality and mobilizing international support. In addition, certain linguistic strategies were constructed, emphasizing similar values with the audience and reshaping the discourse of the war between Russia and Ukraine. The research concluded that through his speech, President Volodymyr Zelenskiy managed to influence the UK parliament members as the audience and further shaped the discourse of the war between Russia and Ukraine wherein Russia is portrayed as the culprit assailing the core value of humanity and Ukraine, on the other hand, is depicted as the victim.